A new multisource and high‐frequency approach to measuring δ2H and δ18O in hydrological field studies. Issue 11 (20th November 2013) - Pangle, Luke A.; Klaus, Julian; Berman, Elena S. F.; Gupta, Manish; McDonnell, Jeffrey J.
<x xml:space="preserve">Abstract</x> [1] Measurements of δ2H and δ18O in isotope‐based field studies have fundamentally improved our understanding of water flow and transport time scales in soils and headwater catchments. Until recently, however, technical constraints have limited the temporal resolution at which water samples could be collected and analyzed. We introduce a new sample acquisition system—consisting of a four‐channel peristaltic pump, custom flow manifold, and CTC LCPAL auto‐sampler—that is paired with a field‐deployable laser spectrometer (LGR LWIA). Our system enables high‐frequency (subhourly) measurement of δ2H and δ18O in as many as four water sources. We deployed the system at a field site in Corvallis, OR, USA, where we measured the δ2H and δ18O composition of precipitation and the drainage from two lysimeters. The system produced δ2H and δ18O time series for precipitation and drainage from each lysimeter at a temporal frequency of one sample every 34 min, which, on average, corresponded to 0.84, 0.63, and 0.48 mm of precipitation or lysimeter drainage per sample. The high‐frequency data showed substantially greater short‐term variability than observed when sampling at successively longer time intervals. The system and sampling configuration are versatile and can be adapted to sample multiple water flows at variable frequencies depending on the characteristic transit times of each source.